2013
DOI: 10.1101/gad.213207.113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for dual roles of Aar2p in U5 snRNP assembly

Abstract: Yeast U5 small nuclear ribonucleoprotein particle (snRNP) is assembled via a cytoplasmic precursor that contains the U5-specific Prp8 protein but lacks the U5-specific Brr2 helicase. Instead, pre-U5 snRNP includes the Aar2 protein not found in mature U5 snRNP or spliceosomes. Aar2p and Brr2p bind competitively to a C-terminal region of Prp8p that comprises consecutive RNase H-like and Jab1/MPN-like domains. To elucidate the molecular basis for this competition, we determined the crystal structure of Aar2p in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 60 publications
2
46
0
1
Order By: Relevance
“…53,54 Structural analyses have shown that Aar2 contains a globular portion and a flexible, C-terminal extension. 41,55,56 The globular part of Aar2 binds the linker, endonuclease, and RH domains of Prp8, while its C-terminal extension spirals along the Prp8 reverse transcriptase domain and across the RH domain, where it connects an extended hairpin of the RH domain with the β-barrel core of the Jab1 domain. 55,56 The Prp8 Jab1 domain is thereby bound to the RH domain in a manner that sterically precludes binding of Brr2.…”
Section: Parallels To the Mechanism Of Jab1-mediated Brr2 Inhibition mentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Structural analyses have shown that Aar2 contains a globular portion and a flexible, C-terminal extension. 41,55,56 The globular part of Aar2 binds the linker, endonuclease, and RH domains of Prp8, while its C-terminal extension spirals along the Prp8 reverse transcriptase domain and across the RH domain, where it connects an extended hairpin of the RH domain with the β-barrel core of the Jab1 domain. 55,56 The Prp8 Jab1 domain is thereby bound to the RH domain in a manner that sterically precludes binding of Brr2.…”
Section: Parallels To the Mechanism Of Jab1-mediated Brr2 Inhibition mentioning
confidence: 99%
“…41,55,56 The globular part of Aar2 binds the linker, endonuclease, and RH domains of Prp8, while its C-terminal extension spirals along the Prp8 reverse transcriptase domain and across the RH domain, where it connects an extended hairpin of the RH domain with the β-barrel core of the Jab1 domain. 55,56 The Prp8 Jab1 domain is thereby bound to the RH domain in a manner that sterically precludes binding of Brr2. 55,56 Phosphorylation of Aar2 at serine 253, possibly aided by additional phosphorylation at other residues, leads to a conformational change that reduces its affinity for Prp8, and thereby allows Brr2 to bind.…”
Section: Parallels To the Mechanism Of Jab1-mediated Brr2 Inhibition mentioning
confidence: 99%
“…Another category of splicing factors that appear to be nearly absent in C. merolae is snRNP biogenesis proteins, the factors involved in initial assembly of snRNPs. The U2 protein Cus2, Aar2 from the cytoplasmic form of U5, Snu40 from the nuclear U5, Sad1 from the tri-snRNP, and the SMN protein required for correct Sm ring assembly in humans were not detected in C. merolae (59)(60)(61). SMN may be rendered unnecessary by the absence of stem-loops 3′ of the Sm binding site in C. merolae snRNAs.…”
Section: Dead Box Proteinsmentioning
confidence: 99%
“…However, initial assembly of yeast U5 snRNP in the cytoplasm leads to a pre-U5 particle that contains the assembly factor Aar2 instead of Brr2. [34][35][36][37][38][39] Thus, Brr2 is transported to the nucleus independent of other U5 snRNP components 35 and its helicase activity may have to be shut off during this phase to avoid detrimental off-target effects. Once assembled in the nucleus, mature U5 snRNP joins the U4/U6 di-snRNP to form the U4/U6 U5 trisnRNP, in which Brr2 already encounters its U4/U6 di-snRNA substrate before incorporation into the spliceosome.…”
Section: Brr2 Requires Tight Regulationmentioning
confidence: 99%